National Geographic Magazine and the Power of Media: How an Elite Society Influenced American Perception - Welsch, Michelle (Crossing the Border: International Journal of Interdisciplinary Studies, 2015)
The history of the National Geographic Magazine has largely evaded the same readers who have adored its editions. Originally intended as a private platform for a select group of white bureaucrats and Washington-D.C. elite, the National Geographic Society achieved commercial success once it included the general public. In time, its publications made foreign lands and scientific discovery accessible to the masses. The magazine’s articles thrilled the American audience as readers could browse foreign destinations from the safety of their homes. Fascination with the elite combined with powerful platforms of photography and text influenced perception of portrayed subjects. "Exotic" topics established a division between observer and the observed, and published content revealed undertones of racial and gender hierarchy. Early editions provide evidence that caution reader of the impact media can have both on and within cultures and the accompanying importance of questioning the intent of publications. Crossing the Border: International Journal of Interdisciplinary Studies Vol.3(1) 2015: 3-10